PERAN GURU DALAM UPAYA PEMBENTUKAN KARAKTER DISIPLIN DAN TANGGUNG JAWAB ANAK DI MIN 7 ACEH TIMUR - Nurhaida, Nurhaida (Faculty of Tarbiyah nad Teacher Training, 2023)
The purpose of this study was to find out 1) The Role of Islamic Religious Education Teachers in Efforts to Form Discipline Character, 2) The Role of Islamic Education Teachers in the Formation of Responsibility Character, 3) Supporting and Inhibiting Factors in Efforts to Form Discipline and Responsibility Character. The research method uses a qualitative approach to data obtained from people and observable behavior. Data derived from manuscripts, interviews, notes, fields and documentation are described so as to provide clarity on the situation and reality. The results of the study of the Role of Islamic Religious Education Teachers in the Formation of Discipline Character. After conducting the research, it was found that there were many roles for teachers to instill the character of discipline, namely: a. Role as a model and role model, by giving examples of punctuality when coming to school or entering class b. Role as a model and role model, by giving an example of going to the mosque when prayer time arrives, early so that children can imitate. c. Role as a model and role model, with examples of dressing neatly according to schedule. d. The role as an educator, with the provision of assignment deadlines. The role of the teacher in the effort to form the Character of Responsibility. Furthermore, regarding the several roles carried out to form the character of responsibility, namely: a. The role as an educator, by giving the task of being a ceremonial officer whose schedule rotates per class. b. The role as an educator, by giving assignments at school and homework. c. The role as a motivator, by providing motivation for the importance of instilling a sense of responsibility. Supporting and Inhibiting Factors in Efforts to Form the Character of Discipline and Responsibility. Several factors support the formation of the character of discipline and responsibility. a. An exemplary teacher. b. Parents who can guide their children when at home. While the inhibiting factor is a. Peers, who have not been good. b. Unfavorable environment at home.